2018
DOI: 10.15171/hpp.2018.15
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural adaption, validity and reliability of a Hindi versionof the Corah’s Dental Anxiety Scale

Abstract: Background: An appropriate scale to assess the dental anxiety of Hindi speaking population is lacking. This study, therefore, aims to evaluate the psychometric properties of Hindi version of one of the oldest dental anxiety scale, Corah’s Dental Anxiety Scale (CDAS) in Hindi speaking Indian adults.Methods: A total of 348 subjects from the outpatient department of a dental hospital in India participated in this cross-sectional study. The scale was cross-culturally adapted by forward and backward translation, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(59 reference statements)
0
3
0
3
Order By: Relevance
“…In recent years, China is one of the few countries with high-speed development in the world, and Chinese society changes very fast. People need to adapt to the changing society, which is also a risk factor for anxiety disorders (38). This may be a reason for changing the order of anxiety and mood disorders.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, China is one of the few countries with high-speed development in the world, and Chinese society changes very fast. People need to adapt to the changing society, which is also a risk factor for anxiety disorders (38). This may be a reason for changing the order of anxiety and mood disorders.…”
Section: Resultsmentioning
confidence: 99%
“…This might have been because the females were more prone to social avoidance and loneliness than males. Some studies suggest that women are more prone to social anxiety than men [31,32]. And evidence also indicates that females are more likely to report loneliness than males [33].…”
Section: Discussionmentioning
confidence: 99%
“…Individual differences in solitude behaviors, particularly concerning gender and age, exist [29,30]. Some evidence suggests that females exhibit higher levels of loneliness and social anxiety compared to males [31][32][33]. However, some studies have shown that males are more likely to report loneliness and adopt social avoidance strategies than females [34,35].…”
Section: Influence Of Gender and Age On Solitudementioning
confidence: 99%
“…Los ítems del módulo DAS presentaron cargas o saturaciones de factor de 0,65 a 0,83 lo que indica una fuerte relación de cada pregunta con el constructo ansiedad dental. Estos resultados son similares a los obtenidos por Jain y Tandon (22) con un autovalor de 2,441 que representó el 61,019% de varianza total.…”
Section: Sig (Bilateral)unclassified
“…Este valor indica que el instrumento es homogéneo, es decir, todos los ítems del cuestionario miden ansiedad dental. El α obtenido en esta investigación fue similar a los encontrados en otros estudios de validación del DAS, como en Brasil (23) donde obtuvieron un α de 0,83 o en India (22) , con un α de 0,782.…”
Section: Sig (Bilateral)unclassified